Magnetic inhomogeneities of soliton and breather type in magnetics with local nonhomogeneities of anisotropy - Ekomasov, E.G.; Azamatov, Sh.A.; Murtazin, R.R. (Functional Materials, 2008)
Using numerical methods, the peculiarities of domain wall transition through the two-dimensional region of magnetic anisotropy constant inhomogeneity has been considered. The origination and evolution of pulson type magnetic inhomogeneities localized in this region have been studied. Із застосуванням числових методів розглянуто особливості проходження доменної межі через двовимірну область неоднорідності константи магнітної анізотропії. Досліджено зародження та еволюція локалізованої магнітної неоднорідності типу пульсону у цій області. С помощью численных методов рассматриваются особенности прохождения доменной границы через двумерную область неоднородности константы магнитной анизотропии. Исследовано зарождение и эволюция локализованной магнитной неоднородности типа пульсона в этой области.